La crisi climatica è grave, ma non tutto è perduto - Antonio Scalari (Università degli Studi di Torino, 2021)
If we had to condense the latest report of the Intergovernmental Panel on Climate Change (IPCC 2021), published last August, into a title, it might be this: science confirms what we already knew. The report is a confirmation because it states what was already evidence: "there is no question that human activities are responsible for climate change". But its relevance lies precisely in this: it presents a large body of data that updates and enriches knowledge, in that process of acquiring new evidence and discussing and reviewing it, which is a fundamental aspect of the collective work of the scientific community.